Heat flow data of RV Sonne cruise SO222 - Norbert Kaul; Achim J Kopf (PANGAEA, 2019)
Temperature gradients and in-situ thermal conductivity, measured with the Bremen heat flow probe. There are 21 channels, spaced 0.26 cm.
Supplement to: Kopf, Achim J; Asshoff, Kira; Belke-Brea, M; Bergenthal, Markus; Bohrmann, Gerhard; Bräunig, Anja; Düßmann, Ralf; Feseker, Tomas; Fleischmann, Timo; Franke, Philipp; Geprägs, Patrizia; Hammerschmidt, Sebastian; Heesemann, Bernd; Herschelmann, Oliver; Hüpers, Andre; Ikari, Matt J; Kaszemeik, Kai; Kaul, Norbert; Kimura, Toshinori; Kitada, Kazuya; Klar, Steffen; Lange, Matthias; Madison, Melissa; Mai, Anh Hoang; Noorlander, Cornelis; Pape, Thomas; Rehage, Ralf; Reuter, Christian; Rosiak, Uwe; Saffer, Demian M; Schmidt, Werner; Seiter, Christian; Spiesecke, Ulli; Stachowski, Adrian; Ojima, Takanori; Tryon, Michael; Vahlenkamp, Maximilian; Wei, Jiayong; Wiemer, Gauvain; Wintersteller, Paul; Zarrouk, Marcel (2013): Report and preliminary results of R/V SONNE cruise SO222. MEMO: MeBo drilling and in situ Long-term Monitoring in the Nankai Trough accretionary complex, Japan. Leg A: Hong Kong, PR China, 09.06.2012 - Nagoya, Japan, 30.06.2012. Leg B: Nagoya, Japan, 04.07.2012 - Pusan, Korea, 18.07.2012. Berichte aus dem MARUM und dem Fachbereich Geowissenschaften der Universität Bremen, 297, 121 pp, urn:nbn:de:gbv:46-00103543-13